Behavioral Complications of Frontal Lobe Seizures - J Gordon Millichap (Pediatric Neurology Briefs)
A 13-yr-old girl with marked behavioral and selective cognitive deficits associated with partial complex seizures of frontal lobe origin is reported from the Depts of Neurology, Psychiatry and Pediatrics, Harbor-UCLA Medical Center, 1000 W Carson St, Torrance, CA.